Descolonizando la cooperación cultural, revitalizando las epistemologías del Sur: Tradiciones orales indígenas y afrodescendientes en Centroamérica - Muñoz Muñoz, Marianela (CIICLA, Universidad de Costa Rica, 2019)
From 2009 to 2012, the “Cultural Revitalization and Creative Productive Development on the Caribbean coast of Nicaragua” program aimed to promote and revitalize cultural expressions, including oral traditions, of Indigenous and Black communities. This paper reflects some of its achievements, contradictions, and lessons. Building from experiences on the UNESCO team, and employing an ethnographic approach, I first expose how these processes underlie the daily struggle of Indigenous and Black people against colonization and Mestizo/Western hegemony in Nicaragua. Second, I delve into how the experience challenged our understanding of international cooperation in Central America, as well as my own positionality as an external and Mestiza researching with (not about) subaltern populations. My argument is that cultural revitalization processes of oral traditions not only entail the emergence of alternative epistemologies (from the South), but also destabilize the colonialist structure of cultural cooperation programs, and the identities of the collaborators.